Distinct modes of death in human neural stem and glioblastoma cells irradiated with carbon-ion radiation and gamma-rays. (1st February 2020) - Yokota, Yuichiro; Wada, Yutaka; Funayama, Tomoo
Abstract: Purpose: Accumulated damage in neural stem cells (NSCs) during brain tumor radiotherapy causes cognitive dysfunction to the patients. Carbon-ion radiotherapy can reduce undesired irradiation of normal tissues more efficiently than conventional photon radiotherapy. This study elucidates the responses of NSCs to carbon-ion radiation. Methods: Human NSCs and glioblastoma A-172 cells were irradiated with carbon-ion radiation and γ-rays, which have different linear-energy-transfer (LET) values of 108 and 0.2 keV/ μ m, respectively. After irradiation, growth rates were measured, apoptotic cells were detected by flow cytometry, and DNA synthesizing cells were immunocytochemically visualized. Results: Growth rates of NSCs and A-172 cells were decreased after irradiation. The percentages of apoptotic cells were remarkably increased in NSCs but not in A-172 cells. In contrast, the fractions of DNA synthesizing A-172 cells were decreased in a dose-dependent manner. These results indicate that apoptosis induction and DNA synthesis inhibition contribute to the growth inhibition of NSCs and glioblastoma cells, respectively. In addition, high-LET carbon ions induced more profound effects than low-LET γ-rays. Conclusions: Apoptosis is an important clinical target to protect NSCs during brain tumor radiotherapy using carbon-ion radiation as well as conventional X-rays.